The Influence of Nationalism on Consumers Loyalty : Taking Multinational Corporations’ Sustainable Development in China as an Example - Bo, Wu; Hamrila, Abdul Latip; Xiaoran, Li (Scientific Research Publishing, 2023)
Based on the influence of nationalism on Chinese consumers’ brand loyalty, specifically in regard to multinational retail enterprises in China. The study utilized qualitative research strategies, and data was collected using questionnaires. The study found that nationalism has a direct impact on Chinese consumers’ brand preferences and loyalty. Chinese consumers are more likely to select domestic brands over foreign ones when making purchasing decisions, and this preference is largely driven by a sense of national pride and loyalty. In order to achieve sustainable development in China, multinational companies must desalinate their nationality attributes and build themselves into international companies. The findings of this study are as follows: 1) Consumers with higher education background are less vulnerable to economic nationalism; 2) Middle-aged consumers are more vulnerable to the impact of cost-effectiveness than economic nationalism; 3) Male consumer loyalty is more vulnerable to nationalism than female consumer loyalty in China; 4) Without the influence of the Black Swan incident, consumer satisfaction plays a mediating role in the process of nationalism affecting consumer loyalty